Sociology of Interdisciplinarity The Dynamics of Energy Research - Silvast, Antti; Foulds, Chris (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"Even though I've been involved in interdisciplinary energy research for more than 20 years, this book is an eye opener for me." - Tanja Winther, Professor, University of Oslo, Norway. "Silvast and Foulds recuperate the critical side of social sciences and bring it into the discussions of what interdisciplinary research can be." - David Hess, Professor of Sociology, Vanderbilt University, USA This Open Access book builds upon Science and Technology Studies (STS) and provides a detailed examination of how large-scale energy research projects have been conceived, and with what consequences for those involved in interdisciplinary research, which has been advocated as the zenith of research practice for many years, quite often in direct response to questions that cannot be answered (or even preliminarily investigated) by disciplines working separately. It produces fresh insights into the lived experiences andactual contents of interdisciplinarity, rather than simply commentating on how it is being explicitly advocated. We present empirical studies on large-scale energy research projects from the United Kingdom, Norway, and Finland. The book presents a new framework, the Sociology of Interdisciplinarity, which unpacks interdisciplinary research in practice. This book will be of interest to all those interested in well-functioning interdisciplinary research systems and the dynamics of doing interdisciplinarity, including real ground-level experiences and institutional interdependencies. Antti Silvast holds a researcher position in the Department of Interdisciplinary Studies of Culture, at the Norwegian University of Science and Technology (NTNU). He is a Sociologist examining energy infrastructure, most recently smart systems, methodology, and energy modelling. Chris Foulds is an Associate Professor at Anglia Ruskin University's Global Sustainability Institute (Cambridge, UK). He is an interdisciplinary Environmental Social Scientist researching how society and everyday life intersect with energy policies, governance, consumption, and the built environment.